Identification of Grade XI Students' Misconceptions on Thermochemistry Using a Five-Tier Diagnostic Test at SMAN 2 Siak Hulu - Novia Cristi Br Pasaribu; Sri Haryati; Dedi Futra (Darul Yasin Al Sys, 2026)
Misconceptions in thermochemistry remain a persistent challenge in chemistry education because they can impede conceptual understanding and adversely affect learning outcomes. This study aimed to identify Grade XI students’ misconceptions about thermochemistry and determine their underlying sources using a five-tier diagnostic test at SMAN 2 Siak Hulu. A descriptive quantitative design was employed, involving 100 students from Classes XI-4, XI-5, and XI-6 who had studied thermochemistry. Data were collected using a 15-item five-tier diagnostic test covering seven thermochemistry concepts and supplemented with structured interviews. The findings revealed misconceptions across all seven concepts, with an average prevalence of 18%, categorized as low. The highest prevalence was identified for thermochemical equations (23%), whereas the lowest was found for heat and energy (9%). Students’ own reasoning was the predominant source of misconceptions (82.13%), followed by textbooks, teachers, peers, and the internet. These findings demonstrate the utility of the five-tier diagnostic test in identifying misconceptions and tracing their underlying sources. The study provides an empirical basis for teachers to develop targeted instructional strategies that prevent and remediate misconceptions, thereby strengthening students’ conceptual understanding of thermochemistry.